Earth and Fiber. - Resim ve Heykel Müzesi, Ankara (Ankara : Sanart '92, 1992)
Taylan Erder, Ferhan ; Furtun, Candeger ; Guidi, Nedda ; Köker, Azade ; Abasiyanik Kurtic, Melike ; Link, Kurt ; Mestre, Enrique ; Hydman-Vallie, Ulrica ; De Amaral, Olga ; Balpinar, Belkis ; Decoster, Jean ; Heybroek-Ulysse Plaud, Mieke ; Kobayashi, Naomi ; Hui Shi
Earth and Fiber, Resim ve Heykel Müzesi, Ankara, 6.10 - 30.10.1992
boek